Global Networks and Local Medicine: A Review of Su Jing's Ten Records of Western Medicine's Arrival in China - ZHANG, Min (Journal of Research for Christianity in China (JRCC), 2023)
Su Jing, Ten Records of Western Medicine in China. Beijing: Zhonghua Book Company, 2020. Includes black-and-white illustrations and tables. 290,000 characters. Price: 68 yuan.